No Easy Walk to Freedom - Mandela, Nelson 1918-2013 (London Mandarin, 1990)
Offers your students stories, poetry, biographical writings and essays from across Africa. This title includes work from nearly 40 writers from 19 different countries.
A Mandarin Paperback
Keywords: South Africa -- Race Relations -- Apartheid